Gestational exposure to polystyrene microplastics incurred placental damage in mice: Insights into metabolic and gene expression disorders - Zhe Wang; Runyan Shi; Ruimin Wang; Zhenzhu Ma; Shuo Jiang; Fengquan Zhang; Weidong Wu (Ecotoxicology and Environmental Safety)
As an emerging environmental pollutant, microplastics have attracted increasing attention to their potential health hazards. However, the current understanding about the toxicity and health implications, especially about developmental toxicity with exposure to microplastics is quite limited. In the current study, we aimed to scrutinize the deleterious effects of polystyrene microplastics (PSMPs) with different sizes (0.1 and 5 μm) on the placenta that plays crucial role in fetal development, following oral exposure during gestational stages. The results showed that two sizes of PSMPs could distribute in mouse placental tissues, and nanosized PSMPs (0.1 μm) exhibited greater capability to penetrate the placenta and deposit in the liver and brain of fetuses than microsized PSMPs (5 μm). Importantly, only 0.1 μm PSMPs induced a decrease in the junctional area, a reduction in the labyrinthine vascularization and an increase in cell apoptosis in the placenta, accompanied by fetal developmental impairments. The results of metabolome and transcriptome uncovered that 0.1 μm PSMP exposure caused changes in metabolic and gene profiles of placental tissues, across multiple pathways such as vascular supply, nutrient absorption and transportation and amino acid metabolism. Overall, our results confirmed that maternal PSMP exposure led to placental damages associated with metabolic and gene expression disorders. This study would provide new insights into the developmental impacts of microplastic consumption during gestation.